Method for manufacturing electrode for electrochemical device

By using acrylic adhesives and high-temperature hot calendering process in the manufacture of lithium-sulfur battery electrodes, the complex drying process in the manufacture of water-based adhesive electrodes is solved, and electrodes with low moisture content and high adhesion strength are realized, and production efficiency and economy are improved.

CN119547226APending Publication Date: 2025-02-28LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202480002902.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-13
Filing Date
2024-02-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

When manufacturing lithium sulfur battery electrodes, the use of aqueous adhesives has problems such as complex drying process, time and cost.

Method used

The electrode adhesive containing an acrylic adhesive is used, and the high-temperature hot calendering process is used to calender at a temperature of 105°C or above to remove moisture in the electrode, simplify the process and reduce costs.

Benefits of technology

The production of low moisture content electrodes without drying process is achieved, which improves production efficiency and economy, while ensuring high adhesion strength and stability of the electrodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a method for manufacturing an electrode, the method comprising the steps of: applying an electrode-forming slurry on at least one surface of a current collector; and calendering the current collector coated with the electrode-forming slurry, in which the electrode-forming slurry contains an electrode active material and an electrode binder, in which the electrode binder contains an acrylic binder, and in which the calendering is performed at a temperature of 105 DEG C or more, whereby in electrode manufacturing using the aqueous binder, the electrode-forming slurry is coated with the electrode-forming slurry, and the electrode-forming slurry is coated with the electrode-forming slurry. An electrode having a low moisture content is manufactured by using a rolling process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing an electrode for an electrochemical device.

[0002] More specifically, the present invention relates to a manufacturing method that can be applied in the manufacture of lithium-sulfur batteries.

[0003] This application claims priority to Korean Patent Application No. 2023-0032605 filed in Korea on March 13, 2023, the disclosure of which is incorporated herein by reference. Background Art

[0004] As the application range of lithium secondary batteries is expanded not only to mobile electronic devices but also to electric vehicles (EVs) and energy storage systems (ESSs), the demand for lithium secondary batteries with high capacity, high energy density, and long life is increasing.

[0005] Among various types of lithium secondary batteries, lithium-sulfur batteries are battery systems that use sulfur compounds containing sulfur-sulfur (SS) bonds as positive electrode active materials and lithium metal as negative electrode active materials. The advantages of lithium-sulfur batteries are that sulfur, the main component of the positive electrode active material, has a low atomic weight, is abundant in nature, can be widely found worldwide, and is inexpensive, non-toxic, and environmentally friendly. In addition, among the secondary batteries developed so far, lithium-sulfur batteries have attracted much attention due to their higher capacity than other battery systems.

[0006] The sulfur used in lithium-sulfur batteries has an electrical conductivity of about 5×10 -30 S / cm is a poor conductor because the electrons generated by the electrochemical reaction cannot move freely. Therefore, the sulfur-containing material is combined with a conductive material such as carbon that provides electrochemical reaction sites to form a sulfur-carbon composite material used as a positive electrode active material.

[0007] On the other hand, during discharge, the lithium-sulfur battery undergoes oxidation at the negative electrode active material lithium by releasing electrons into lithium cations, and undergoes reduction at the positive electrode active material sulfur-based material by accepting electrons. Through the reduction reaction, the sulfur-based material is converted into sulfur anions through an SS bond that accepts two electrons. The lithium cations generated by the oxidation reaction of lithium migrate to the positive electrode through the electrolyte, and combine with the sulfur anions generated by the reduction reaction of the sulfur compound to form a salt. Specifically, sulfur has a cyclic S8 structure before discharge, and it is converted into lithium polysulfide (Li2S x , x = 8, 6, 4, 2), and is completely reduced to lithium sulfide (Li2S). However, lithium polysulfide easily dissolves into the electrolyte during charging and discharging, resulting in battery capacity decay and battery degradation. In order to solve the problem of lithium polysulfide dissolution, sulfur is loaded into the pores of different types of porous carbon materials in the positive electrode.

[0008] Under this circumstance, in order to use the sulfur-carbon composite material including the porous carbon material in the positive electrode, a binder with high bonding strength is required due to its low density and large surface area. Under this circumstance, many studies have been conducted on various binders, and in particular, aqueous binders have been intensively studied to achieve low binder content and high sulfur loading.

[0009] However, when an aqueous binder is used to manufacture an electrode, a drying process is required to remove the residual moisture in the electrode, leaving many aspects to be improved when the aqueous binder is used in the electrode, such as complex manufacturing equipment and increased time and cost in the manufacturing process. Therefore, there are still many challenges in using aqueous binders. Summary of the invention

[0010] Technical issues

[0011] The present invention aims to solve the above-mentioned problems, and therefore the present invention aims to provide a novel method for manufacturing an electrode for an electrochemical device by a simple and direct process using an aqueous binder.

[0012] More particularly, the present invention aims to provide a method for manufacturing an electrode that is easy to apply an aqueous binder to a lithium-sulfur battery.

[0013] Technical Solution

[0014] According to one aspect of the present invention, a method for producing an electrode for an electrochemical device according to the following embodiment is provided.

[0015] The method for producing an electrochemical device electrode according to the first embodiment includes the following steps:

[0016] coating the electrode forming slurry on at least one surface of the current collector, and

[0017] The current collector coated with the electrode forming slurry is rolled,

[0018] The electrode forming slurry comprises an electrode active material and an electrode binder,

[0019] wherein the electrode binder comprises an acrylic binder, and

[0020] The calendering is carried out at a temperature above 105°C.

[0021] According to the second embodiment, in the first embodiment, the content of the acrylic binder may be 0.1 wt % or more based on the total weight of the electrode active material and the electrode binder.

[0022] According to a third embodiment, in the first or second embodiment, the acrylic adhesive may include a polymer including at least one of (meth)acrylic acid, (meth)acrylamide, or acrylonitrile as a monomer, a copolymer thereof, or a mixture thereof.

[0023] According to a fourth embodiment, in any one of the first to third embodiments, the electrode binder may further include at least one of a cellulose-based binder or a rubber-based binder.

[0024] According to a fifth embodiment, in any one of the first to fourth embodiments, the electrode binder may include an acrylic binder, a cellulose binder, and a rubber binder, and the content of the acrylic binder may be 10 wt % to 95 wt % based on the total weight of the acrylic binder, the cellulose binder, and the rubber binder.

[0025] According to a sixth embodiment, in any one of the first to fifth embodiments, the cellulose-based binder may include carboxymethyl cellulose, carboxyethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, nitrocellulose, diethylaminoethyl cellulose, or a mixture thereof.

[0026] According to a seventh embodiment, in any one of the first to sixth embodiments, the rubber-based adhesive may include styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, butyl rubber, fluororubber, acrylic rubber, or a mixture thereof.

[0027] According to an eighth embodiment, in any one of the first to seventh embodiments, the calendering may be performed at a temperature of 105°C to 140°C.

[0028] According to a ninth embodiment, in any one of the first to eighth embodiments, the moisture content in the electrode after rolling may be 1,000 ppm or less.

[0029] According to a tenth embodiment, in any one of the first to ninth embodiments, the moisture content in the electrode before rolling may be 1,000 ppm or more.

[0030] According to an eleventh embodiment, in any one of the first to tenth embodiments, the method may further include the step of cutting the rolled electrode.

[0031] According to a twelfth embodiment, in any one of the first to eleventh embodiments, after the calendaring step, substantially, the method may not further include a step of drying the electrode.

[0032] According to a thirteenth embodiment, in any one of the first to twelfth embodiments, the electrode active material may include a sulfur-containing compound.

[0033] According to a fourteenth embodiment, in any one of the first to thirteenth embodiments, a weight ratio of the electrode active material to the electrode binder may be 90:10 to 98:2 (electrode active material:electrode binder).

[0034] According to another aspect of the present invention, an electrode for an electrochemical device according to the following embodiment is provided.

[0035] The electrode for an electrochemical device according to the fifteenth embodiment is produced by the method according to any one of the first to fourteenth embodiments.

[0036] Beneficial Effects

[0037] According to the method for preparing an electrode binder according to one aspect of the present invention, a method for manufacturing an electrode can be provided, in which the moisture content in the electrode is low after calendering, thereby omitting a drying process, thereby saving cost and time.

[0038] In particular, by using an aqueous binder, electrodes having high electrode adhesion strength can be manufactured in a cost- and time-efficient manner.

[0039] Furthermore, electrodes with high electrode adhesion strength for lithium-sulfur battery applications can be manufactured. DETAILED DESCRIPTION

[0040] Hereinafter, the present invention will be described in detail. However, the present invention is not limited to the following description, and various modifications or selective use can be made to each element as needed. Therefore, it should be understood that the present invention includes all variants, equivalents or substitutes included in the technical aspects and scope of the present invention.

[0041] Unless the context clearly indicates otherwise, the terms “comprise” or “comprising” when used in the present specification specify the presence of stated elements, but do not exclude the presence or addition of one or more other elements.

[0042] According to one aspect of the present invention, there are provided a method for producing an electrode for an electrochemical device and an electrode for an electrochemical device produced by the method.

[0043] The electrochemical device includes any device in which an electrochemical reaction occurs, and specific examples may include any type of primary battery, secondary battery, fuel cell, solar cell, or capacitor such as a supercapacitor. In particular, among these secondary batteries, lithium secondary batteries including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, or lithium sulfur secondary batteries are preferred. The detailed structure of the electrochemical device is well known, so its description is omitted.

[0044] The electrochemical device may be included in the energy storage system as a unit cell, and its use is not limited to a specific application. The detailed structure of the energy storage system is well known, so the description thereof is omitted.

[0045] The method for manufacturing an electrode for an electrochemical device comprises the following steps:

[0046] coating an electrode-forming slurry on at least one surface of a current collector; and

[0047] The current collector coated with the electrode forming slurry is rolled,

[0048] The electrode forming slurry comprises an electrode active material and an electrode binder,

[0049] The electrode binder comprises an acrylic binder, and

[0050] The calendering is carried out at a temperature above 105°C.

[0051] The electrode forming slurry forms an electrode active material layer on at least one surface of a current collector, and is a solution containing an electrode active material and an electrode binder.

[0052] In one embodiment of the present invention, coating of the electrode forming slurry may be performed by any method generally used for coating an electrode forming slurry on a current collector, and the coating means and method are not particularly limited to specific kinds.

[0053] In one embodiment of the present invention, the electrode forming slurry can be formed by adding an electrode active material and an electrode binder to a solvent simultaneously or sequentially. In addition, in another embodiment of the present invention, the electrode forming slurry can be formed by mixing an electrode active material with a dispersion in which an electrode binder is dispersed or a binder solution in which an electrode binder is dissolved. In any case, the electrode forming slurry contains a predetermined material in a liquid state.

[0054] In one embodiment of the present invention, after coating the electrode forming slurry on at least one surface of the current collector, before the calendering step, the method may further include pre-drying the current collector coated with the electrode forming slurry to prepare a preliminary electrode. In this case, the pre-drying is performed to fix the electrode forming slurry coated on at least one surface of the current collector to prevent it from flowing out of the coating area, and any method generally used for fixing the electrode forming slurry can be used without limitation.

[0055] In one embodiment of the present invention, the electrode binder comprises an aqueous binder to improve electrode adhesion strength and prevent environmental problems caused by non-aqueous binders.

[0056] In particular, the electrode forming slurry includes an acrylic binder as an electrode binder. When the acrylic binder is included as the electrode binder, an electrode having improved electrode adhesion strength may be manufactured, but the effect of the present invention is not limited thereto.

[0057] In one embodiment of the present invention, an acrylic binder is one of the aqueous binders used to manufacture an electrode, and is a general term for binders containing at least one acrylic structure (-C=CC(O)O-) or acrylic precursor structure in the structure of the binder. The acrylic precursor structure is a general term for structures that form acrylic structures by chemical modification. The acrylic precursor structure may include, for example, a structure derived from acrylonitrile (CH2CHCN) as a raw material.

[0058] In one embodiment of the present invention, based on the total weight of the electrode active material and the electrode binder, the content of the acrylic binder can be, for example, 0.1% by weight or more. Specifically, based on the total weight of the electrode active material and the electrode binder, the content of the acrylic binder can be 0.1% by weight to 10% by weight, specifically 0.5% by weight to 5% by weight, 1% by weight to 5% by weight, 1% by weight to 2.5% by weight, 1% by weight to 2.0% by weight, 1.5% by weight to 2.0% by weight, or 1.5% by weight to 1.8% by weight. When the content of the acrylic binder is within the above range, this can have a beneficial effect on the loading amount of the active material in the resulting electrode and the electrode adhesion strength, but the present invention is not limited thereto.

[0059] In one embodiment of the present invention, the acrylic adhesive may include, for example, a polymer containing at least one of (meth) acrylic acid, (meth) acrylamide or acrylonitrile as a monomer, a copolymer thereof or a mixture thereof. Specifically, the acrylic adhesive may include poly(meth) acrylic acid, poly(meth) acrylamide, acrylamide-acrylic acid copolymer, polyacrylonitrile or a mixture thereof, but is not limited thereto.

[0060] In another embodiment of the present invention, the electrode binder may include other aqueous binders used to manufacture the electrode in addition to the acrylic binder.

[0061] The aqueous adhesive other than the acrylic adhesive may include, for example, a cellulose-based adhesive or a rubber-based adhesive.

[0062] Therefore, in one embodiment of the present invention, the electrode binder may further include at least one of a cellulose-based binder or a rubber-based binder, but is not limited thereto.

[0063] Cellulose adhesives are a general term for adhesives containing cellulose or its derivative structure in the structure of the adhesive. For example, the cellulose adhesives may include carboxymethyl cellulose, carboxyethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, nitrocellulose, diethylaminoethyl cellulose or a mixture thereof.

[0064] The rubber-based binder is a general term for rubber-based binders used to manufacture electrodes. The rubber-based binder may include, for example, styrene-butadiene rubber, acrylonitrile-butadiene, acrylonitrile-butadiene-styrene rubber, butyl rubber, fluororubber, acrylic rubber or a mixture thereof, but is not limited thereto.

[0065] In one embodiment of the present invention, butyl rubber refers to a rubber substituted with a butyl group, and may include, for example, a rubber containing at least one butyl group as a substituent in styrene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene or acrylonitrile-butadiene-styrene rubber.

[0066] In one embodiment of the present invention, fluororubber refers to a rubber substituted by fluorine (F) atoms, and may include, for example, a rubber containing at least one fluorine atom as a substituent in styrene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber or acrylonitrile-butadiene-styrene rubber.

[0067] In one embodiment of the present invention, acrylic rubber refers to a rubber substituted with a (meth) acrylate group, and may include, for example, a rubber containing at least one (meth) acrylate group as a substituent in styrene rubber, butadiene rubber, styrene-butadiene rubber, acrylonitrile-butadiene or acrylonitrile-butadiene-styrene rubber. For example, the acrylic rubber may include styrene-butyl acrylate rubber.

[0068] In one embodiment of the present invention, the electrode binder may include two types of binders, an acrylic binder and a cellulose binder. In this case, the acrylic binder and the cellulose binder may be included in a weight ratio of 1:3 to 3:1 or 1:2 to 2:1, for example 1:1, but the present invention is not limited thereto.

[0069] In another embodiment of the present invention, the electrode binder may include two types of binders, an acrylic binder and a rubber binder. In this case, the acrylic binder and the rubber binder may be included in a weight ratio of 1:3 to 3:1 or 1:2 to 2:1, such as 1:1, but the present invention is not limited thereto.

[0070] In another embodiment of the present invention, the electrode binder may include three types of binders: an acrylic binder, a cellulose binder, and a rubber binder.

[0071] In one embodiment of the present invention, when the electrode binder comprises an acrylic binder, a cellulose binder and a rubber binder, the content of the acrylic binder may be 10% to 95% by weight based on the total weight of the acrylic binder, the cellulose binder and the rubber binder. Specifically, based on the total weight of the acrylic binder, the cellulose binder and the rubber binder, the content of the acrylic binder may be 10% to 90% by weight, 10% to 70% by weight, 10% to 50% by weight, 15% to 50% by weight, 20% to 50% by weight, 25% to 45% by weight, 30% to 45% by weight, 35% to 45% by weight or 40% to 45% by weight.

[0072] In one embodiment of the present invention, based on the total weight of acrylic adhesive, cellulose adhesive and rubber adhesive, the content of cellulose adhesive may be 0.1 wt % to 25 wt %, 0.5 wt % to 25 wt %, 1 wt % to 25 wt %, 5 wt % to 25 wt %, 5 wt % to 20 wt %, 5 wt % to 15 wt %, 5 wt % to 10 wt % or 1 wt % to 5 wt %. In addition, based on the total weight of acrylic adhesive, cellulose adhesive and rubber adhesive, the content of rubber adhesive may be 0.1 wt % to 65 wt %, 4.9 wt % to 60 wt %, 5 wt % to 55 wt %, 10 wt % to 50 wt %, 20 wt % to 50 wt %, 30 wt % to 50 wt %, 40 wt % to 50 wt % or 45 wt % to 50 wt %.

[0073] When the three types of binders are included in the above amounts, this may have a beneficial effect on the electrode adhesion strength and the moisture content in the resulting electrode, but the present invention is not limited thereto.

[0074] In another embodiment of the present invention, in addition to the above-mentioned aqueous binder, the electrode binder may further include a non-aqueous binder without hindering the purpose of the present invention.

[0075] In one embodiment of the present invention, the non-aqueous binder may include, for example, a fluorine-containing binder commonly used to make electrodes. The fluorine-containing binder may include, for example, polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE), polytetrafluoroethylene (PTFE) or a mixture thereof, but is not limited thereto.

[0076] In one embodiment of the present invention, the electrode forming slurry may further include a conductive material in addition to the electrode active material and the electrode binder without hindering the purpose of the present invention. The conductive material may include any type of conductive material generally used in electrodes for electrochemical devices without limitation.

[0077] Acrylic adhesive has the property of absorbing moisture in the air by its unique structure, and therefore, for example, it is used as a moisture absorbent material in a wide variety of applications. Therefore, acrylic adhesive is known as a material for manufacturing electrodes due to high bonding strength, but due to its inherent moisture absorption ability, a drying process is required to remove moisture after manufacturing the electrode.

[0078] According to one embodiment of the present invention, the current collector coated with the electrode forming slurry can be dried at a high temperature, specifically at a temperature above 105°C, to remove moisture from the electrode binder, especially the acrylic binder. Therefore, the manufacturing method of the electrode is characterized in that calendering and drying are performed simultaneously. According to one embodiment of the present invention, calendering at a high temperature can be referred to as "hot calendering".

[0079] According to one embodiment of the present invention, the temperature of the hot rolling step is preferably within a temperature range in which sulfur contained as a positive electrode active material does not volatilize. For this reason, the rolling may be preferably performed at a temperature of, for example, 150°C or less, 145°C or less, 140°C or less, preferably 135°C or less, but the present invention is not limited thereto.

[0080] In one embodiment of the present invention, calendering can be carried out at a temperature of, for example, above 110°C, above 115°C, above 120°C, specifically at 120°C to 150°C, 120°C to 145°C, 120°C to 140°C, 120°C to 135°C, 120°C to 130°C, 125°C to 135°C or 130°C.

[0081] In one embodiment of the present invention, the calendering step can be performed using a calender. Specifically, the calender can be operated while supplying heat to the roller so that the roller temperature becomes high, especially up to the above-mentioned temperature.

[0082] In another embodiment of the present invention, the calendering step may be performed using a hot press. In this case, the press for hot pressing may have a plate-like shape, but may also have a roll-like shape, but the present invention is not limited thereto.

[0083] In one embodiment of the present invention, as described above, the calendaring step is performed to remove moisture from the electrode binder, particularly an acrylic binder, and is preferably performed in a dry environment.

[0084] In one embodiment of the present invention, the calendering step may be performed under a dew point condition of less than 0° C. The dew point may be measured by a common method, for example, using a dew point meter with a thermometer and a hygrometer.

[0085] In another embodiment of the present invention, the calendering step can be carried out under an absolute humidity condition of 0.00377 kg / kg or less. In this case, the absolute humidity represents a measurement value of the amount of water vapor (kg) per 1 kg of dry air and can be measured by a method generally used to measure absolute humidity.

[0086] According to one embodiment of the present invention, the moisture content in the electrode forming slurry coated on one surface of the current collector may be significantly reduced through the calendaring step.

[0087] For example, the moisture content in the electrode after rolling may be 1,000 ppm or less. Specifically, the moisture content in the electrode after rolling may be 800 ppm or less, 600 ppm or less, 500 ppm or less, or 300 ppm or less. According to one aspect of the present invention, preferably, the moisture content in the resulting electrode is zero or too low to be measured by a moisture measurement method, and the lower limit of the moisture content in the electrode is not limited to a specific range, preferably 0 ppm.

[0088] According to one embodiment of the present invention, the difference in moisture content in the electrode before and after the calendering step can be made large.

[0089] For example, the moisture content in the electrode before rolling may be 1,000 ppm or more, specifically greater than 1,000 ppm, for example, 1,200 ppm or more, and the moisture content in the electrode after rolling may be 1,000 ppm or less, for example, 800 ppm or less.

[0090] In this specification, the moisture content in the electrode can be measured using a Karl Fischer titrator. Specifically, a Karl Fischer titrator (Metrohm 756KF Coulometer) can be used. The electrode to be measured can be punched into a circular shape with a diameter of 14φ to prepare 10 samples, and the moisture content can be the average value of three measurements of each sample.

[0091] In one embodiment of the present invention, when the calendering step is performed, the thickness of the electrode can be reduced, thereby improving the electrical and chemical properties of the electrode. Specifically, the calendering step can be performed under a compression rate of 5% or more according to the following mathematical formula 1. For example, the calendering step can be performed under a compression rate of 5% to 10%.

[0092] [Mathematical formula 1]

[0093] Compression rate (%) = [(thickness of electrode before calendering - thickness of electrode after calendering) / thickness of electrode before calendering] × 100

[0094] In this specification, the thickness of the electrode refers to the sum of the thickness of the current collector and the thickness of the electrode active material layer, and can be measured by using a method commonly used to measure the thickness of each component of the electrode. For example, the thickness of the electrode can be measured using a SEM cross-sectional image of the electrode or a thickness meter (Mitutoyo).

[0095] According to one embodiment of the present invention, the manufacturing method of the electrode may include: unwinding the wound current collector; coating the electrode to form a slurry; and rolling to form a long electrode. Therefore, the manufacturing method of the electrode may also include a cutting step of cutting the rolled electrode into a plurality of unit electrodes.

[0096] Typically, after calendering, the method for manufacturing an electrode further includes a drying step to completely remove the moisture remaining in the electrode before, after, or during cutting the electrode. However, according to the method for manufacturing an electrode of one aspect of the present invention, the calendering and drying of the electrode can be performed in a single step by a hot calendering step, so that the method can substantially not include a step of drying the electrode after the calendering step.

[0097] In this specification, substantially not including an electrode drying step means that after the electrode is rolled, no step of supplying dry air or additional heat to the rolled electrode through a dry air supplier or a heat supplier to remove residual moisture is performed, and the process of becoming drier by natural evaporation of residual moisture from the rolled electrode is not excluded.

[0098] In one embodiment of the present invention, the electrode for an electrochemical device may be a positive electrode or a negative electrode.

[0099] In one embodiment of the present invention, when the electrode for an electrochemical device is a positive electrode, the electrode active material may include a positive electrode active material commonly used in the art.

[0100] In another embodiment of the present invention, the electrode may be a positive electrode for use in a lithium-sulfur battery, and the electrode active material may include a sulfur-containing compound.

[0101] In yet another embodiment of the present invention, the electrode may be a positive electrode for a lithium-sulfur battery, and the electrode active material may include a porous carbon support and a sulfur-containing compound supported in at least one of inner pores or outer pores of the porous carbon support.

[0102] In one embodiment of the present invention, the sulfur-containing compound can be used as a positive electrode active material for a lithium-sulfur battery and can include, for example, inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x, (1 < x ≤ 8), a disulfide compound, or a mixture thereof, but the present invention is not limited thereto.

[0103] In one embodiment of the present invention, when the electrode for an electrochemical device is a negative electrode, the electrode active material may include a negative electrode active material commonly used in the art.

[0104] In another embodiment of the present invention, the electrode may be a negative electrode for a lithium-sulfur battery.

[0105] In one embodiment of the present invention, the current collector is not limited to a specific type and may include a current collector having high electrical conductivity and not causing chemical changes in the corresponding battery.

[0106] According to another aspect of the present invention, there is provided an electrode for an electrochemical device manufactured by the above manufacturing method.

[0107] The electrode includes a current collector and an electrode active material layer on at least one surface of the current collector.

[0108] The electrode active material layer may include an electrode active material and an electrode binder, and has a structure in which the electrode active material is bound by the electrode binder.

[0109] In the present invention, the electrode binder is characterized by including an acrylic binder.

[0110] According to the present invention, the electrode includes an acrylic binder, but achieves a low moisture content, thereby ensuring high assembly stability when used in an electrochemical device, but the present invention is not limited thereto.

[0111] Hereinafter, the present invention will be described in detail through experimental examples.

[0112] Experimental Example 1

[0113] [Manufacture of Positive Electrode]

[0114] According to the composition in Table 1 below, a sulfur-carbon composite material (S / C 70:30) as an electrode active material and an electrode binder were added to water (H2O) as a solvent, and mixed using a planetary dispersion mixer (PD mixer) to prepare a positive electrode forming slurry for a lithium-sulfur battery.

[0115] Specifically, a positive electrode forming slurry was prepared by kneading and mixing a part of the binder and the solvent (water) with the active material, and then adding the remaining binder and solvent for further mixing.

[0116] The cathode forming slurry was applied to an aluminum foil current collector using a coater (Mathis AG), predried in an oven at 50° C. and hot-rolled using a calender at 130° C. in a drying chamber (speed: 50 Hz) to obtain a cathode for a lithium-sulfur battery.

[0117] [Evaluation of electrode properties]

[0118] Evaluation of moisture content before and after calendering

[0119] The moisture content in the electrode was measured using a Karl Fischer titrator (Metrohm 756KF coulometer) immediately before and after calendering, and the results are shown in Table 2 below.

[0120] Specifically, each electrode immediately before and after rolling was punched into a circular shape with a diameter of 14φ to prepare 10 samples, and the moisture content was an average value of three measurements.

[0121]

[0122]

[0123] As can be seen from Tables 1 and 2 above, it was confirmed that the calendering conditions were appropriate because the calendering conditions did not cause a change in the sulfur loading before and after calendering.

[0124] In addition, when polyacrylic acid (PAA) is not included as an electrode binder as in Comparative Example 1, the moisture content in the electrode before calendering is less than 1,000 ppm, while when polyacrylic acid is included as an electrode binder as in Example 1, the moisture content in the electrode before calendering is higher than 1,000 ppm, so a process of removing moisture is required, and the moisture content is significantly reduced through the hot calendering step, indicating that it can be used in a battery assembly without a drying process.

[0125] Experimental Example 2

[0126] [Manufacturing of positive electrode]

[0127] An electrode forming slurry having the same composition as that of Example 1 of Experimental Example 1 was prepared, applied onto an aluminum foil current collector using a coater (Mathis AG), and pre-dried in an oven at 50° C. to obtain a preliminary electrode.

[0128] An electrode was manufactured using the obtained preliminary electrode through the subsequent processes shown in Table 3 below, and the moisture content in the electrode was evaluated. The results are shown in Table 3.

[0129] In Table 3 below, "room temperature calendering" means calendering using a 25° C. calendering machine, and "secondary drying" means secondary drying in an oven at 80° C. for 2 hours without a calendering process.

[0130] In order to compare the evaluation results, the evaluation results of Example 1 are also shown in Table 3 below.

[0131]

[0132] As can be seen from Table 3 above, it is confirmed that when PAA is used to manufacture an electrode, room temperature calendering requires a subsequent drying process, while hot calendering at 130°C can achieve a low moisture content without a subsequent drying process. In particular, it is confirmed that the secondary drying process requiring a long time can be omitted, thereby significantly saving the cost and time of the electrode manufacturing method.

[0133] Experimental Example 3

[0134] [Manufacturing of positive electrode]

[0135] An electrode forming slurry was prepared according to the composition shown in Table 4 below, the prepared electrode forming slurry was coated on an aluminum foil and pre-dried, and the subsequent processes shown in Table 5 below were performed to manufacture an electrode.

[0136] [Evaluation of electrode properties]

[0137] Evaluation of moisture content

[0138] The moisture content in the electrode before and after the subsequent process was measured using a Karl Fischer titrator (Metrohm 756KF coulometer), and the results are shown in Table 5 below.

[0139] Evaluation of electrode adhesion strength

[0140] The electrode adhesion strength of the electrode prepared above was measured by the following method, and the results are shown in Table 5 below.

[0141] Specifically, the electrode to be measured was punched into a size of 2 cm × 11 cm, pasted so that the active material layer of the electrode adhered to a glass slide with double-sided tape, and then pulled apart 90° at a speed of 30 mm / s using a UTM machine to measure the peel strength.

[0142]

[0143]

[0144] It was confirmed from the above Tables 4 and 5 that when the slurry was formed using an electrode having a higher PAA content, the moisture content in the electrode before calendaring was greater than 2,000 ppm, ie, the moisture content of the electrode was much higher, compared to Example 1.

[0145] It was confirmed that when an electrode having a high moisture content was heat-calendered at 130° C., the resulting electrode had suitable electrode adhesion strength and a moisture content as low as 1,000 ppm or less to be used in a battery assembly.

[0146] Through the above experiments, it was confirmed that the method for manufacturing an electrode according to one aspect of the present invention can manufacture an electrode with a low moisture content without requiring a long secondary drying step when manufacturing an electrode using an aqueous binder.

[0147] In particular, it was confirmed that, even in the case where the amount of the acrylic binder having high bonding performance was high, an electrode having excellent performance in terms of electrode adhesion strength and moisture content could be manufactured.

[0148] Experimental Example 4

[0149] [Manufacturing of positive electrode]

[0150] An electrode forming slurry having the same composition as that of each of Example 1 and Comparative Example 1 of Experimental Example 1 was prepared, coated on an aluminum foil current collector using a coater (Mathis AG), and pre-dried in an oven at 50° C. to obtain a preliminary electrode.

[0151] An electrode was produced using the obtained preliminary electrode through the subsequent processes shown in Table 6 below, and the change in the sulfur loading amount in the electrode before and after rolling was evaluated, and the results are shown in Table 6 below.

[0152] The change in the sulfur loading amount in the electrode before and after rolling was evaluated as follows.

[0153] First, the prepared electrode was punched into a 5 cm × 5 cm (25 cm 2 ) to prepare a total of 10 sheets. Among them, 5 sheets were used to measure the load in the electrode before calendering, and 5 sheets were used to measure the load in the electrode after calendering, and calendering was performed according to the subsequent procedures shown in Table 6 below.

[0154] Solid powder collected by taking the active material layer from the current collector of the prepared electrode or the rolled electrode was analyzed by inductively coupled plasma optical emission spectrometry (ICP-OES) to measure the weight of sulfur (S) based on the total weight of the active material layer and the area (25 cm2) of the positive electrode active material layer. 2 ×5, total 125 cm 2 ) The change in sulfur weight before and after calendering was measured, and the evaluation results are shown in the following Table 6.

[0155]

[0156] It was confirmed from the results of Table 6 above that when the hot rolling temperature was too high, sulfur loss in the active material layer might occur.

Claims

1. A method for manufacturing an electrode for an electrochemical device, the method comprising the following steps: coating an electrode-forming slurry on at least one surface of a current collector; and rolling the current collector coated with the electrode forming slurry, wherein the electrode forming slurry comprises an electrode active material and an electrode binder, wherein the electrode binder comprises an acrylic binder, and The calendering is performed at a temperature above 105°C. 2 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein the content of the acrylic binder is 0.1% by weight or more based on the total weight of the electrode active material and the electrode binder. 3 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein the acrylic binder comprises a polymer containing at least one of (meth)acrylic acid, (meth)acrylamide or acrylonitrile as a monomer, a copolymer thereof or a mixture thereof. 4 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein the electrode binder further comprises at least one of a cellulose-based binder and a rubber-based binder.

5. The method for producing an electrode for an electrochemical device according to claim 1, wherein the electrode binder comprises an acrylic binder, a cellulose binder and a rubber binder, and The content of the acrylic adhesive is 10 wt % to 95 wt % based on the total weight of the acrylic adhesive, the cellulose adhesive and the rubber adhesive.

6. The method for producing an electrode for an electrochemical device according to claim 4, wherein the cellulose-based binder comprises carboxymethyl cellulose, carboxyethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, nitrocellulose, diethylaminoethyl cellulose or a mixture thereof.

7. The method for manufacturing an electrode for an electrochemical device according to claim 4, wherein the rubber-based binder comprises styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, butyl rubber, fluororubber, acrylic rubber or a mixture thereof. 8 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein the rolling is performed at a temperature of 105° C. to 140° C. 9 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein a moisture content in the electrode after the rolling is 1,000 ppm or less. 10 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein the moisture content in the electrode before the rolling is 1,000 ppm or more.

11. The method for manufacturing an electrode for an electrochemical device according to claim 1, further comprising the following steps: The rolled electrode is cut. 12 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein after the rolling step, the method does not substantially further include a step of drying the electrode. 13 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein the electrode active material comprises a sulfur-containing compound. 14 . The method for producing an electrode for an electrochemical device according to claim 1 , wherein a weight ratio of the electrode active material to the electrode binder is 90:10 to 98:2 (the electrode active material:the electrode binder). 15 . An electrode for an electrochemical device, the electrode for an electrochemical device being produced by the production method according to claim 1 .